Analysis of the Quality of PKN STAN Tax Clinic Services - Budiarsih, Riani; Liyana, Nur Farida (Ilomata International Journal of Tax and Accounting, 2025)
The tax clinic is a program initiated by the PKN STAN Tax Center in collaboration with KPP Pratama Pondok Aren since 2023. This initiative is run by student volunteers and assist taxpayers. Student-run tax clinics are becoming increasingly common in higher education settings, but research evaluating the service quality of volunteer-based tax programs remains very limited in Indonesia. Yet volunteer-based services play a strategic role in supporting tax literacy and compliance. Therefore, this study aims to fill this gap by evaluating the quality of services provided by PKN STAN tax clinic volunteers to taxpayers. This research employs a quantitativeresearch approach. Data were collected through questionaires distributed to taxpayers who utilized the tax clinic services at KPP Pratama Pondok Aren. The data were analyzed using average scoring and service quality (SQ) analysis methods. The results show that the average service quality scores fall above 4 on a 5-point scale, indicating that taxpayers perceive the service as important and are generally satisfied with the performance. Despite positive performance perceptions, the overall service quality gap score was -0.02. This suggests that, while taxpayers appreciate the service, there are still unmet expectations, and several aspect of the tax clinic services require improvement. Thus, this study provide practical recommendations for enhancing service delivery so that could serve as a reference for other educational agencies aiming to implement similar program.